Multicolor, Cell-Impermeable, and High Affinity BACE1 Inhibitor Probes Enable Superior Endogenous Staining and Imaging of Single Molecules - Stockinger, Florian; Poc, Pascal; Möhwald, Alexander; Karch, Sandra; Häfner, Stephanie; Alzheimer, Christian; Sandoz, Guillaume; Huth, Tobias; Broichhagen, Johannes (Journal of Medicinal Chemistry, 2024)
The prevailing but not undisputed amyloid cascade hypothesis places the β-site of APP cleaving enzyme 1 (BACE1) center stage in Alzheimer′s Disease pathogenesis. Here, we investigated functional properties of BACE1 with novel tag- and antibody-free labeling tools, which are conjugates of the BACE1-inhibitor IV (also referred to as C3) linked to different impermeable Alexa Fluor dyes. We show that these fluorescent small molecules bind specifically to BACE1, with a 1:1 labeling stoichiometry at their orthosteric site. This is a crucial property especially for single-molecule and super-resolution microscopy approaches, allowing characterization of the dyes′ labeling capabilities in overexpressing cell systems and in native neuronal tissue. With multiple colors at hand, we evaluated BACE1-multimerization by Förster resonance energy transfer (FRET) acceptor-photobleaching and single-particle imaging of native BACE1. In summary, our novel fluorescent inhibitors, termed Alexa-C3, offer unprecedented insights into protein-protein interactions and diffusion behavior of BACE1 down to the single molecule level.
CRIS-Team Scopus Importer:2024-06-21